2016
DOI: 10.1038/modpathol.2016.134
|View full text |Cite
|
Sign up to set email alerts
|

Genetic events in the progression of adenoid cystic carcinoma of the breast to high-grade triple-negative breast cancer

Abstract: Adenoid cystic carcinoma of the breast is a rare histologic type of triple-negative breast cancer with an indolent clinical behavior, often driven by the MYB-NFIB fusion gene. Here we sought to define the repertoire of somatic genetic alterations in two adenoid cystic carcinomas associated with high-grade triple-negative breast cancer. The different components of each case were subjected to copy number profiling and massively parallel sequencing targeting all exons and selected regulatory and intronic regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 63 publications
4
44
0
1
Order By: Relevance
“…Our analyses revealed that, consistent with primary PACs, recurrent PACs showed the canonical alterations affecting PRKD genes, including PRKD1 hotspot E710D mutations or a PRKD2 rearrangement. The maintenance of the highly recurrent/pathognomonic genetic alteration that characterises these tumours in the recurrences and after the acquisition of high-grade histological features is consistent with the observations made in other tumour types driven by pathognomonic genetic alterations, [41][42][43][44] and is consistent with the notion that these alterations constitute drivers of the disease. For instance, in the progression of adenoid cystic carcinomas to high-grade tumours, the MYB-NFIB fusion gene is maintained 41 ; likewise, in the progression of granulosa cell tumours, the FOXL2 C134W mutation is conserved.…”
Section: Discussionsupporting
confidence: 88%
“…Our analyses revealed that, consistent with primary PACs, recurrent PACs showed the canonical alterations affecting PRKD genes, including PRKD1 hotspot E710D mutations or a PRKD2 rearrangement. The maintenance of the highly recurrent/pathognomonic genetic alteration that characterises these tumours in the recurrences and after the acquisition of high-grade histological features is consistent with the observations made in other tumour types driven by pathognomonic genetic alterations, [41][42][43][44] and is consistent with the notion that these alterations constitute drivers of the disease. For instance, in the progression of adenoid cystic carcinomas to high-grade tumours, the MYB-NFIB fusion gene is maintained 41 ; likewise, in the progression of granulosa cell tumours, the FOXL2 C134W mutation is conserved.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to microglandular adenoses/atypical microglandular adenoses and breast acinic cell carcinomas, salivary gland-like tumors of the breast do not resemble conventional triple-negative breast cancers at the genetic level, harbor low levels of genetic instability with few copy number changes (12, 45) and do not harbor highly recurrent TP53 mutations (12). Although those lesions may also, albeit less frequently, progress to high-grade triple-negative breast cancers, there is evidence that those high-grade carcinomas also differ genetically from conventional triple-negative breast cancers (45, 46). Previous observations based on histologic and immunohistochemical analyses have suggested a potential association between microglandular adenosis and adenoid cystic carcinomas (47).…”
Section: Discussionmentioning
confidence: 99%
“…In this cancer, no mutations were observed occurring in triple-negative breast cancers such as TP53 and PIK3CA, whereas it shows somatic mutational heterogeneity affecting the functions of, among others, chromatin remodelling and cell adhesion [10].…”
Section: Microscopic Diagnosticsmentioning
confidence: 99%
“…Also, the frequency of local recurrences was lower after the application of radiotherapy. This is recommended in patients who have undergone conserving surgery, especially with the presence of positive margins [2,10,18].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation